The effect of pramlintide (amylin analogue) treatment on bone metabolism and bone density in patients with type 1 diabetes mellitus - Borm, Anne Katrin; Klevesath, Martina; Borcea, Valentin; Kasperk, Christian; Seibel, Markus J.; Wahl, Peter; Ziegler, Reinhard; Nawroth, Peter Paul (Hormone and metabolic research, 1999)
Amylin is a 37-amino-acid peptide related to CGRP and calcitonin. It is co-secreted with insulin from pancreatic β-cells. Amylin is deficient with type 1 diabetes mellitus. To study the in vivo effects of amylin in humans, diabetic patients are an adequate model of chronic amylin deficiency. We investigated the effect of a 12 months pramlintide therapy (amylin analogue) on bone metabolism in patients with type 1 diabetes mellitus.